2015
DOI: 10.1371/journal.pone.0137990
|View full text |Cite
|
Sign up to set email alerts
|

Global Identification of MicroRNAs and Their Targets in Barley under Salinity Stress

Abstract: Salinity is a major limiting factor for agricultural production worldwide. A better understanding of the mechanisms of salinity stress response will aid efforts to improve plant salt tolerance. In this study, a combination of small RNA and mRNA degradome sequencing was used to identify salinity responsive-miRNAs and their targets in barley. A total of 152 miRNAs belonging to 126 families were identified, of which 44 were found to be salinity responsive with 30 up-regulated and 25 down-regulated respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 55 publications
3
46
0
1
Order By: Relevance
“…Species and genotype specific miRNA families are more likely to target specific enzymes associated with special pathways than conserved miRNAs. Deng and colleagues showed that miR-n05 was responsive to salt stress in barley and targeted the transcript for the enzyme enolase which functions in carbohydrate metabolism in plants by catalyzing the conversion of 2-phosphoglycerate to phosphoenolpyruvate (Van der Straeten et al 1991; Deng et al 2015). An understanding of both conserved and genotype or species specific miRNA and their targets is crucial for interpreting abiotic stress interrelated molecular mechanisms in the Triticeae .…”
Section: Mirnas As Regulatory Keystones In Cropsmentioning
confidence: 99%
See 4 more Smart Citations
“…Species and genotype specific miRNA families are more likely to target specific enzymes associated with special pathways than conserved miRNAs. Deng and colleagues showed that miR-n05 was responsive to salt stress in barley and targeted the transcript for the enzyme enolase which functions in carbohydrate metabolism in plants by catalyzing the conversion of 2-phosphoglycerate to phosphoenolpyruvate (Van der Straeten et al 1991; Deng et al 2015). An understanding of both conserved and genotype or species specific miRNA and their targets is crucial for interpreting abiotic stress interrelated molecular mechanisms in the Triticeae .…”
Section: Mirnas As Regulatory Keystones In Cropsmentioning
confidence: 99%
“…Salinity stress may arise due to the accumulation of salt in the soil over time as a consequence of climatological events, primary salinity, or through human activities which cause an imbalanced soil in salt content and generate the salinity stress, secondary salinity (Parihar et al 2015). Each year, more than 900 million ha of land is affected by salinity stress, which carries an associated yield loss (Deng et al 2015). The effect of salinity stress on food production is predicted to increase with the effect of climate change (Wang et al 2003).…”
Section: Mirnas Associated With Abiotic Stress Responses In the Tritimentioning
confidence: 99%
See 3 more Smart Citations